2022
DOI: 10.1126/science.abn2600
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of oxybenzone sunscreen to phototoxic glucoside conjugates by sea anemones and corals

Abstract: The reported toxicity of oxybenzone-based sunscreens to corals has raised concerns about the impacts of ecotourist-shed sunscreens on corals already weakened by global stressors. However, oxybenzone’s toxicity mechanism(s) are not understood, hampering development of safer sunscreens. We found that oxybenzone caused high mortality of a sea anemone under simulated sunlight including ultraviolet (UV) radiation (290 to 370 nanometers). Although oxybenzone itself protected against UV-induced photo-oxidation, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…In the recent ten years, a large body of research has documented that most BTR- and BP-UVFs have persistence, bioaccumulation, and multiple toxicities, including strong endocrine activity, genotoxicity, cytotoxicity, neurotoxicity, mutagenicity, and reproductive and developmental toxicities, as well as ecotoxicity, further raising significant concerns regarding their health and ecological risks. A compelling example is oxybenzone (BP-3), which can be converted to phototoxins, posing a mortal threat to vulnerable coral reefs . In view of their hazardous nature, worldwide regulatory agencies are beginning to act, and a series of BTR- and BP-UVFs are currently within the scope of international regulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent ten years, a large body of research has documented that most BTR- and BP-UVFs have persistence, bioaccumulation, and multiple toxicities, including strong endocrine activity, genotoxicity, cytotoxicity, neurotoxicity, mutagenicity, and reproductive and developmental toxicities, as well as ecotoxicity, further raising significant concerns regarding their health and ecological risks. A compelling example is oxybenzone (BP-3), which can be converted to phototoxins, posing a mortal threat to vulnerable coral reefs . In view of their hazardous nature, worldwide regulatory agencies are beginning to act, and a series of BTR- and BP-UVFs are currently within the scope of international regulations.…”
Section: Introductionmentioning
confidence: 99%
“…A compelling example is oxybenzone (BP-3), which can be converted to phototoxins, posing a mortal threat to vulnerable coral reefs. 18 In view of their hazardous nature, worldwide regulatory agencies are beginning to act, and a series of BTRand BP-UVFs are currently within the scope of international regulations. For example, several BTR-UVFs, including 2- (benzotriazol-2-yl)-4,6-di-tert-tertbutylphenol (UV-320), 2,4di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol (UV-327), and 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV-328), are listed as "substances of very high concern" under the European Union REACH (Registration, Evaluation, and Authorization of Chemicals) regulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5,6 A number of organic UV filters have come under scrutiny in recent years due to concerns about their safety to humans as well as aquatic environments and organisms. [7][8][9][10][11] With this in mind, research into understanding the fundamental photochemistry and photophysics of current organic UV filters as well as for novel alternatives is crucial to the development of sunscreens with improved safety profiles. 12 Toxicological studies and the monitoring of biological endpoints are also essential to assess the true safety of a candidate organic UV filter.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches implicated the metabolic products of BP-3, phototoxic oxybenzone-glucoside conjugates, can be considered as a culprit of the increasing bleaching rate of corals (Hansel, 2022;Vuckovic et al, 2022). On the contrary, it also has been revealed that Symbiodiniaceae could protect the coral host from the toxic effects of BP-3 metabolites by sequestering the phototoxins (Vuckovic et al, 2022). However, the protection mechanism by which Symbiodiniaceae protects the host remains unclear.…”
Section: Introductionmentioning
confidence: 99%